The effectiveness of prenatal yoga in reducing anxiety levels among pregnant women in primary health care: A literature review - Desak Made Paris Okarini; Ni Gusti Kompiang Sriasih; Ni Luh Putu Sri Erawati (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Anxiety in pregnant women is a common maternal mental health issue, particularly during the third trimester. This condition can negatively impact both maternal and fetal health, leading to sleep disturbances, elevated blood pressure, preterm labor, and postpartum depression. One widely used non-pharmacological intervention to reduce anxiety in pregnant women is prenatal yoga. Purpose: to analyze the effectiveness of prenatal yoga in reducing anxiety levels among pregnant women in primary healthcare settings. Method: This study employed a literature review using a narrative approach. Articles were electronically searched via the Google Scholar, PubMed, and ScienceDirect databases. Inclusion criteria included research articles published between 2021 and 2026, written in Indonesian or English, available in full text. The article selection process utilized the PRISMA flow diagram, resulting in 8 articles meeting the inclusion criteria. Results: The findings indicate that all articles state prenatal yoga is effective in reducing anxiety levels in pregnant women, particularly during the third trimester. The mechanism by which prenatal yoga reduces anxiety is related to stimulation of the parasympathetic nervous system, a decrease in cortisol levels, and an increase in endorphins and serotonin, which play a role in creating a sense of comfort and calm. Conclusion: Prenatal yoga is an effective, safe, and easily implementable nonpharmacological intervention in primary healthcare to help reduce anxiety levels in pregnant women. Prenatal yoga can be recommended as part of integrated antenatal care to support maternal mental health and improve the quality of life for pregnant women